Prevalence of third-generation cephalosporin-resistant Enterobacterales colonization on hospital admission and ESBL genotype-specific risk factors: a cross-sectional study in six German university hospitals. (16th March 2020) - Rohde, Anna M; Zweigner, Janine; Wiese-Posselt, Miriam; Schwab, Frank; Behnke, Michael; Kola, Axel; Schröder, Wiebke; Peter, Silke; Tacconelli, Evelina; Wille, Thorsten; Feihl, Susanne; Querbach, Christiane; et al.
Abstract: Objectives: To assess the admission prevalence of third-generation cephalosporin-resistant Enterobacterales (3GCREB) and to assess whether risk factors vary by β-lactamase genotype. Methods: Adult patients were recruited within 72 h of admission to general wards of six university hospitals in 2014 and 2015. Rectal swabs were screened for 3GCREB and isolates were analysed phenotypically and genotypically. Patients were questioned on potential risk factors. Multivariable analyses were performed to identify risk factors for 3GCREB colonization and for specific β-lactamases. Results: Of 8753 patients screened, 828 were 3GCREB positive (9.5%). Eight hundred and thirteen isolates were available for genotyping. CTX-M-15 was the most common ESBL (38.0%), followed by CTX-M-1 (22.5%), CTX-M-14 (8.7%), CTX-M-27 (7.5%) and SHV-ESBL (4.4%). AmpC was found in 11.9%. Interestingly, 18 Escherichia coli isolates were AmpC positive, 12 of which (67%) contained AmpC on a gene of plasmid origin [CMY ( n = 10), DHA ( n = 2)]. Risk factors for 3GCREB colonization varied by genotype. Recent antibiotic exposure and prior colonization by antibiotic-resistant bacteria were risk factors for all β-lactamases except CTX-M-14 and CTX-M-27. Travel outside Europe was a risk factor for CTX-M-15 and CTX-M-27 [adjusted OR (aOR) 3.49, 95% CI 2.88–4.24 and aOR 2.73, 95% CI 1.68–4.43]. A previous stay in a long-term care facility was associated with CTX-M-14 (aOR 3.01, 95% CI 1.98–4.59). A preceding hospital stay in Germany increased the risk of CTX-M-15 (aOR 1.27, 95% CI 1.14–1.41), while a prior hospital stay in other European countries increased the risk of SHV-ESBL colonization (aOR 3.85, 95% CI 1.67–8.92). Conclusions: The detection of different ESBL types is associated with specific risk factor sets that might represent distinct sources of colonization and ESBL-specific dissemination routes.